Implementation of robot operating system in smart garbage bin robot with obstacle avoidance system - Wong, Seng Cheong; Syafiq Fauzi, Kamarulzaman; Md Arafatur, Rahman (Institute of Electrical and Electronics Engineers Inc., 2020)
Hygiene problem is a no solution problem in Malaysia due to the littering of the citizens. To solve the problem, the government has increased the garbage bin in the public space to encourage the citizens to throw rubbish in the garbage bin. However, the task of collecting the garbage will become difficult due to a large number of garbage bins. Thus, autonomous garbage bin that has the mobility to transport itself from one location to another should be the trend in future. In this paper, we proposed for developing an intelligent garbage bin robot utilizing robot operating system (ROS) for autonomous garbage retrieval. Using the robot operating system, the microcontroller was allowed to control the robot for running capacity detection, global positioning, garbage delivery and obstacle avoidance at the same time. The results shows that the robot was able to operate its bearing adjustment through motor control when confronting an obstacle.